Antibacterial Analysis of Muntingia Calabura (Mansanitas) Ethanolic Flower Extract on Staphylococcus Aureus Using Paper Disc Diffusion Method - Collantes, Franchezka; Tarre, Merriam Danielle (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study aimed to evaluate the antibacterial efficacy of Muntingia calabura ethanolic flower extract against Staphylococcus aureus using the paper disc diffusion method. Anchored on the concept that plant-derived bioactive compounds such as flavonoids, tannins, and polyphenols can inhibit bacterial growth, the research employed an experimental design with three independent trials. The extract was obtained through maceration of flower samples in 96% ethanol, followed by filtration and solvent evaporation, and was tested using standardized microbiological procedures, including the preparation of a bacterial inoculum and the use of a 0.5 McFarland standard. The results revealed measurable zones of inhibition of 29 mm, 31 mm, and 28 mm, with an average of 29 mm, indicating strong antibacterial activity classified as “very active.” No inhibition was observed in the control, confirming that the antimicrobial effect was due to the extract. The findings demonstrated consistent and reproducible antibacterial activity across trials, suggesting the presence of effective bioactive compounds. However, the study was limited by the use of a single extract concentration, a small number of trials, and the absence of compound isolation and inhibitory concentration analysis. The study concludes that Muntingia calabura ethanolic flower extract has significant potential as a natural antibacterial agent. It is recommended that future research explore varying concentrations, identify active compounds, and determine minimum inhibitory and bactericidal concentrations. This study aligns with SDG 3 (Good Health and Well-Being) by contributing to alternative treatments for infectious diseases and SDG 12 (Responsible Consumption and Production) through the use of plant-based resources. It contributes to sustainability by supporting public health solutions and promoting the use of locally available natural resources for accessible and cost-effective antimicrobial development.